Experience of providing dental care in the conditions of the military state - Kaniura, О. А.; Bidenko, Н. В.; Kolenko, Ю. Г.; Filonenko, В. В.; Khrol, Н. С.; Shpak, Д. Ю. (Actual Dentistry, 2022)
Relevance. The state of war had a significant impact on the provision of medical care to the population of Ukraine. Considering that dental care is one of its highly specialized types, the events in the country were fully reflected in it as well. The aim of the study. Summarize and analyze the experience of outpatient dental reception of patients in the conditions of the Dental Medical Center, which is a structural unit of the University Clinic of Bogomolets National Medical University, during the martial law period. Materials and methods. A retrospective analysis of 4,308 medical histories of persons who sought dental care at the Dental Medical Center of Bogomolets National Medical University within two months from the moment martial law was declared in Ukraine (February 28, 2022—April 30, 2022). The results. The work of the Dental Medical Center of Bogomolets National Medical University was restored practically from the first days of the declaration of martial law in Ukraine. For the period from 28.02 to of 30.04.2022 4,308 patients were admitted by the staff of the Dental Medical Center, of which 1,713 (39.8%) were servicemen of the Armed Forces of Ukraine and soldiers of the Territorial Defense. Conclusions. The experience of organizing and conducting an outpatient dental appointment in the conditions of martial law, on the one hand, highlighted the problems of dental care for soldiers and conscripts before the start of a full-scale invasion, and on the other hand, it allowed to develop recommendations regarding the algorithm of the operation of a medical institution in extreme conditions.